Factors influencing the implementation of patient safety culture in mitra sejati hospital, medan city in 2022 - Juang Putra Telaumbanua; Rahmat Dachi; Janno Sinaga; Wisnu Hidayat; Evawani Silitonga (Institute of Computer Science (IOCS), 2023)
The World Health Organization in 2018 collected hospital research figures in several countries, found adverse events in the range of 3.2 -16.6%. Safety culture is concerned with the extent to which the organization prioritizes and supports the improvement of safety safely. The purpose of this research is the factors that influence the implementation of patient safety culture at Mitra Sejati Hospital, Medan City in 2021. The type of research is a quantitative analytic survey using a cross sectional design. The population is nurses and management at Mitra Sejati Medan Hospital, totaling 186 with a sampling technique using random sampling with a total of 149 respondents. The data used include primary data and secondary data. Data analysis used bivariate and multivariate approaches. The results of this study indicate that there is an effect of open communication with p value = 0.022, cooperation within units with p value = 0.000, cooperation between units with p value = 0.002, length of work with p value = 0.048, and the availability of facilities on safety. patients at Mitra Sejati Hospital Medan with p value = 0.010. And the most dominant factor for patient safety at Mitra Sejati Hospital Medan is cooperation within the unit. It is recommended to Mitra Sejati Hospital to improve services in collaboration with all units at the RSU so as to minimize the occurrence of incidents related to patient safety.